Novi pristupi u liječenju hidradenitis suppurativa - Gajanin, Vesna; Baroš, Nikola; Marošević, Goran; Ninković Baroš, Đuka; Balaban, Jagoda (Scripta Medica, 2022)
Background / Aim: Hidradenitis suppurativa (HS) is a chronic inflammatory disease that most often affects apocrine gland-bearing areas of the skin. The treatment depends on the severity of the clinical presentation. The paper objective was to present new modalities in management and treatment of HS.Methods: The subjects in this research included the patients suffering from the severe form of HS, who were treated in the University Clinical Centre of the Republic of Srpska for the past three years. The effect of treatment of HS were monitored. In four patients, biologic therapy with adalimumab or adalimumab biosimilars was administered, while four patients received radiotherapy and 17 of them, were treated surgically. Depending on the type of treatment, the effects of therapy were monitored after 6-12 weeks by using clinical examination and by assessing the disease stage according to the Hurley staging. Due to a small number of subjects, especially in patients treated with biologic and radiotherapy, it was not possible to perform any statistical analysis and the results were presented by description, in tables and photographs.Results: Biologic therapy: Adalimumab was administered subcutaneously 80 mg, twice a month. After 12 weeks, in 4 patients was observed a regression of changes by 60-70 % when compared to previous skin changes. Radiotherapy: the total radiation dose was 5 Gy, distributed in 5 or 10 fractions. After 12 weeks animprovement by 60-70 % was observed. Surgical treatment: after 6-8 weeks, the patients were fully recovered.Conclusions: Application of biologic and radiotherapy after 12 weeks had similar results, ie it brought to regression of changes by 60-70 %. The best results were achieved after surgical treatment of HS.